2019
DOI: 10.1002/ajhb.23304
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and health‐related quality of life in adolescents: A longitudinal analysis from the LabMed Physical Activity Study

Abstract: Objective: The purpose of this study was to examine the longitudinal associations between cardiorespiratory fitness and health-related quality of life (HRQoL) in a sample of adolescents, and to determine whether changes in cardiorespiratory fitness were associated with HRQoL over a 2-year follow-up. Methods: This is a longitudinal analysis with 571 Portuguese adolescents (274 boys and 297 girls) aged 12-18 years. HRQoL was measured with the Kidscreen-10 questionnaire; the 20 m shuttle-run was used to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…Our results con rm and reemphasize previous ndings on the positive association between physical tness and HRQOL in childhood [20,22], adolescence [21,24,47,48], and in the context of childhood and adolescent obesity [24]. In the present analysis, we furthermore found relative physical tness to be the strongest and only remaining determinant of two domains of self-concept: perceived scholastic and social competence.…”
Section: The Association Between Physical Fitness Physical Activity Media Consumption and Psychosocial Healthsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results con rm and reemphasize previous ndings on the positive association between physical tness and HRQOL in childhood [20,22], adolescence [21,24,47,48], and in the context of childhood and adolescent obesity [24]. In the present analysis, we furthermore found relative physical tness to be the strongest and only remaining determinant of two domains of self-concept: perceived scholastic and social competence.…”
Section: The Association Between Physical Fitness Physical Activity Media Consumption and Psychosocial Healthsupporting
confidence: 91%
“…Thus, prior research indicates that it is important to also include physical tness into the analysis of psychosocial health [19,20]. Studies with non-overweight children have yielded promising results in terms of psychosocial improvements associated with increased tness [17,21,22]. Knowing that tness is a mediator in the relationship between childhood and adolescent obesity and self-concept [23] and HRQOL [24,25], supports the need to further investigate its role among the predictors of psychosocial health.Therefore, the aim of this cross-sectional analysis was to examine determinants of weight-speci c HRQOL and subdomains of self-concept in the context of obesity in childhood and adolescence, while considering physical tness as an additional potentially relevant predictor.…”
mentioning
confidence: 99%
“…In this regard, our results demonstrate that physical fitness may be an important contributor to achieving program goals beyond mere weight loss. While its positive effect on physical health and weight management is undisputed, this study, on the one hand, identifies the importance of physical fitness for the personal self-concept and, on the other hand, reemphasizes the relevance of physical fitness for HRQOL in childhood [20], adolescence [19,24], and in the context of obesity [23]. Because it is associated with both physical and psychosocial dimensions [18,21,22], our results hence suggest that a focus on improving fitness could lead to more sustainable therapy outcomes than short-term weight loss [17].…”
Section: Associations Between Physical Fitness Physical Activity and Psychosocial Health Of Children And Adolescents With Obesitymentioning
confidence: 86%
“…Thus, prior research indicates that it is important to also include physical fitness in the analysis of psychosocial health [17]. Studies with non-overweight children have yielded promising results in terms of psychosocial improvements associated with increased fitness [18][19][20]. Knowing that physical fitness is a mediator in the relationship between childhood and adolescent obesity and self-concept [21,22] and HRQOL [15,23,24], supports the need to further investigate its predictive potential for the psychosocial health of affected children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous evidence has shown that physical fitness in children and adolescents is inversely associated with the risk of developing diabetes and obesity, as well as positively associated with skeletal health (Ortega et al, 2008b). Additionally, recent evidence has revealed that physical fitness is also positively associated with mental health and well‐being in adolescents (Bou‐Sospedra, Adelantado‐Renau, Beltran‐Valls, & Moliner‐Urdiales, 2020; Wheatley et al, 2020), suggesting a positive relationship with adolescents’ health‐related quality of life (HRQoL) (Yi, Fu, Burns, & Ding, 2019; Evaristo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%